2022
DOI: 10.4018/978-1-7998-8609-9.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Gender Diversity and Financial Risk

Abstract: This chapter intends to contribute to the analysis of gender diversity and financial risk through a bibliometric review of the existent literature to understand the current state of financial risk research as well as to contribute to the analysis of the influence of gender diversity on financial risk. Although there is extensive research on financial risk, no recent study tries to update the current state of the research over the influence of gender on financial risk practices. This chapter describes the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Several studies Ali et al (2021) and Sun et al (2022) reported that gender diversity positively affects financial performance, thereby preventing companies from bankruptcy. Studies Ali et al (2021) and Teodósio et al (2022) stated that gender diversity can prevent bankruptcy and plays a role in balancing the behaviour of men and women, ensuring stable policies, specifically regarding strategic decisions in maintaining business sustainability.…”
Section: Good Corporate Governancementioning
confidence: 99%
“…Several studies Ali et al (2021) and Sun et al (2022) reported that gender diversity positively affects financial performance, thereby preventing companies from bankruptcy. Studies Ali et al (2021) and Teodósio et al (2022) stated that gender diversity can prevent bankruptcy and plays a role in balancing the behaviour of men and women, ensuring stable policies, specifically regarding strategic decisions in maintaining business sustainability.…”
Section: Good Corporate Governancementioning
confidence: 99%
“…A large body of research has highlighted the effects of RMC gender diversity on the likelihood of financial distress (Chen et al, 2019;Elisa & Guido, 2020;Mittal & Lavina, 2018;Saima & Arefin, 2022b;Teodósio et al, 2022;Zhou, 2019). Mittal and Lavina (2018) empirically examined the effect of board gender diversity on financial distress using the sample of Indianlisted family firms for a period ranging from 2013 to 2016.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…However, there is still limited research on gender diversity in Nigeria regarding risk management committees and the likelihood of firms' financial distress. This is worth assessing as previous studies have suggested that women and men are quite different in respect to risk taking, preference, aversion and tolerance (Elisa & Guido, 2020;Saima & Arefin, 2022;Teodósio et al, 2022;Zalata et al, 2018). Drawing on the NCCG 2018, which serves as an instrumental variable, this study addresses potential endogeneity concerns related to self-selection biases and explores the causal link between risk management committee gender and the likelihood of financial distress.…”
Section: Introductionmentioning
confidence: 99%
“…This means that more women members on the risk committee make the risk committee's oversight of the risk management process more effective. Women are seen as more conscientious and conservative and tend to avoid risk [39]. Women are the right people to provide oversight to management, especially in terms of risk management.…”
Section: Gender Diversitymentioning
confidence: 99%